Fps Moba Video Game Popularity Analysis Using Quantitative Approach: A Case Study Of Apex Legends - Andreas Andreas; Tony Wibowo (Universitas Internasional Batam, 2023)
One of the technology products in the field of entertainment that is most popular among teenagers today is games. One of the most popular games now is Apex Legends, the goal of this research is to answer what makes this game become so popular compared to other games. The quantitative approach was used to gather information about the population’s condition. By using UTAUT2 Model, it was found that the factors that influence Apex Legends popularity are Effort Expectation, Facilitation Condition, and Habit with Effort Expectation having a significance value of 0,043, and both Facility Condition and Habit having a significance value of 0,000. In conclusion, these findings show that Apex Legends is still very much influenced by social factors rather than the mechanic aspects of video games.